STRATEGIC COMPETENCE AS A GUARANTEE OF PROFESSIONAL ACTIVITY OF A MODERN IT SPECIALIST - Volkova Nataliia; Oliinyk Iryna; Karpova Maryna (Alfred Nobel University Publisher, 2023)
The article examines the current problem of professional training of future IT specialists in the context of forming their strategic competence because it is critical for university graduates in the field of IT to be able to strategically plan actions in different ways for effective implementation in their professional activities. Therefore, the strategy of professional activity is carried out by means of separate tactical actions, which collectively make up strategic activity. Thus, s IT specialists' shaping strategic competence allows understanding of which actions are the most important for the realization of the goal and the achievement of professional tasks. It has been established that strategic competence of an IT specialist is a personal integrative creation. This represents the unity of professionally significant qualities, knowledge and skills, with the help of which specialists formulate the strategic goal of work, show a value-motivational attitude to strategic changes and flexibility in behaviour depending on the factors of the external environment, make a reasonable choice and implement strategies depending on the situation, while achieving the effectiveness of the professional activity. The importance of shaping strategic competence in three main sections is substantiated including: elemental (a set of components, the interaction between which ensures the implementation of the relevant activity); functional (methodology for adopting strategies); and procedural (technology for developing and implementing a strategy in the existing environment). It has been proved that a high level of IT specialists' strategic competence ensures the following: determination of the leading goal of professional activity, choosing an effective model of professional behaviour following existing conditions, planning and development of measures for adaptation to conditions of professional activity, implementation of planned professional actions and operations (strategies), etc. The article also presents the main aspects of professional training of future IT specialists. The experience of organizing and implementing university training for future IT specialists shows that a high level of strategic competence makes it possible to choose and prepare the right hardware and software, rational methods for solving professional tasks, allows for the modernization of IT infrastructure, optimization of IT efficiency for innovation. This makes it possible to manage the IT sector, in particular, in the context of IT infrastructure management, IT projects, IT costs, to increase the security and stability of the industry. It is important to define long-term goals, taking into account the phased process of optimizing existing IT systems. A strong emphasis is also placed on the following blocks of scientific knowledge: the use of technologies and algorithms of computational intelligence and intelligent data analysis in the tasks of forecasting, analytics, cluster analysis using software tools to support multidimensional data analysis based on DataMining, TextMining, WebMining technologies, mastering system programming languages and methods of developing online programs, performing parallel and distributed calculations, applying numerical methods and algorithms, etc. The article also provides promising directions for research as a study of the real state of shaping strategic competence of future bachelors in the IT field.